PENERAPAN AMPLIFIED WORD OF MOUTH ANTARA KONSULTAN JAFRA DENGAN CUSTOMER DALAM PEMBENTUKAN CUSTOMER LOYALTY - Simanjuntak, Tasya Irwanty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The beauty industry is increasing and has many competitors, so every beauty industry must have a strategy to build and maintain customer loyalty. As was done by JAFRA Cosmetics, in this research, the researchers were interested in seeing how consultants implemented amplified word of mouth to form customer loyalty. Customer loyalty plays a vital role in the company so that it can help the company's development. The writing of this research discusses how JAFRA Cosmetics implements amplified word of mouth to form customer loyalty. This research aims to determine how JAFRA Cosmetics implements amplified word of mouth to form customer loyalty. This research uses a descriptive qualitative approach with phenomenological methods. Data collection was carried out using structured interviews. The data sources used are primary through interviews with several JAFRA consultant sources and secondary through documentation. The data analysis technique in this research is the interactive analysis model by Miles and Huberman, who state that qualitative data analysis activities are carried out continuously. The results of the data analysis show that there are several ways to spread amplified word of mouth, such as through social media by carrying out regular branding, skin checks to customers, and providing education and testimonials. Therefore, any information supplied by JAFRA consultants gives customers confidence and can attract customers to make purchasing decisions, thereby forming customer loyalty.